Effects of Freezing on the Mechanical Properties of Clay Moraine (Vliyanie Zamorazhivaniya i Ottaivaniya Morennogo Suglinka na Ego Stroitelne Svoistva) - Evdokimov,P. D.; Zauerbrei,I. I. (1972)
The studies conducted have shown that the strength of moraine loam, decreasing appreciably according to superficial visual criteria as a result of the soil's freeze-thaw cycle, is apparently restored if one imparts to the soil a load of 1 kg/sq cm and more. At the design vertical load from a structure equalling 2 kg/sq cm, the strength of the ground under it after compaction will be less than the strength of ground not subjected to frost effect. The necessity for leaving a layer for protection aginst freezing is eliminated. (Author) Draft trans. of Gidrotekhnicheskoe Stroitelstvo (USSR) v19 n2 p26-29 Feb 50.